Tackling COVID‐19 infection through complement‐targeted immunotherapy - Jodele, Sonata (Br J Pharmacol, 2020)
The complement system is an ancient part of innate immunity sensing highly pathogenic coronaviruses by mannan‐binding lectin (MBL) resulting in lectin pathway activation and subsequent generation of the anaphylatoxins (ATs) C3a and C5a as important effector molecules. Complement deposition on endothelial cells and high blood C5a serum levels have been reported in COVID‐19 patients with severe illness, suggesting vigorous complement activation leading to systemic thrombotic microangiopathy (TMA). Complement regulator gene variants prevalent in African‐Americans have been associated with a higher risk for severe TMA and multi‐organ injury. Strikingly, severe acute respiratory syndrome Coronavirus 2 (SARS‐CoV‐2)‐infected African‐Americans suffer from high mortality. These findings allow us to apply our knowledge from other complement‐mediated diseases to COVID‐19 infection to better understand severe disease pathogenesis. Here, we discuss the multiple aspects of complement activation, regulation, crosstalk with other parts of the immune system, and the options to target complement in COVID‐19 patients to halt disease progression and death. LINKED ARTICLES: This article is part of a themed issue on Canonical and non‐canonical functions of the complement system in health and disease. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.14/issuetoc